1961
DOI: 10.1161/01.res.9.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Tension Developed by Papillary Muscles from Hypertrophied Rat Hearts

Abstract: O DETERMINE whether, in certain aspects, hypertrophied heart muscle behaves differently from normal heart muscle simple observations were performed. Papillary muscle strips from the left ventricle of rats, the hearts of which had been caused to hypertrophy, were compared with papillary strips from normal rat hearts by measuring tension developed at various weights in a perfused isolated muscle strip preparation. Having parallel muscle fibers and sharing in hypertrophy of the left ventricle, 1 -2 papillary musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

1968
1968
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…This is in agreement with a number of previous studies (among others, Alpert et al, 1974;Bing et al, 1971;Ring et al, 1978). However, the results conflict with those of Kerr et al (1961), Grimm et al (1963), andWilliams andDeiss (1978). Furthermore, the recent clinical studies by Peterson et al (1978) indicate that, on the average, muscle stiffness remains normal in patients with aortic stenosis although there were isolated cases in which muscle stiffness was abnormal.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This is in agreement with a number of previous studies (among others, Alpert et al, 1974;Bing et al, 1971;Ring et al, 1978). However, the results conflict with those of Kerr et al (1961), Grimm et al (1963), andWilliams andDeiss (1978). Furthermore, the recent clinical studies by Peterson et al (1978) indicate that, on the average, muscle stiffness remains normal in patients with aortic stenosis although there were isolated cases in which muscle stiffness was abnormal.…”
Section: Discussioncontrasting
confidence: 70%
“…It always has been assumed that right and left ventricular muscles have similar mechanical properties (Alpert et al, 1974;Bing et al, 1971;Grimm et al, 1963;Kerr et al, 1961); however, this has never been quantified. Figure 4 demonstrates that normal right and left ventricular muscle stiffness is not statistically different over the stress range 5-25 g/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies reported that contractile function of hypertrophied myocardium was normal or even "supernormal" (1)(2)(3)(4), the methods used to assess contractile state and the manner in which this function was corrected for differences in muscle mass have been criticized. More recently, Spann, Received for publication 10 May 1974 and in revised form 16 August 1974.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to support this impression has been gained primarily from the observation that patients dying with COPD often have left ventricular hypertrophy at postmortem examination (2)(3)(4)(5)(6)(7), and the possible mechanisms for this have been summarized (7). However, the presence of myocardial hypertrophy does not necessarily indicate depressed myocardial function since it has been demonstrated that the hypertrophied myocardium can function normally (8) or even supernormally (9)(10)(11)(12)(13). Furthermore, definitive conclusions concerning left ventricular function in these patients cannot be made from the vast amount of hemodynamic data accumulated from cardiac catheterization studied which have been summarized recently (14).…”
Section: Introductionmentioning
confidence: 99%